2013
DOI: 10.1371/journal.pone.0054176
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Perfluorooctane Sulfonate to Hippocampal Cells in Adult Mice

Abstract: Perfluorooctane sulfonate (PFOS) is a ubiquitous pollutant and found in the environment and in biota. The neurotoxicity of PFOS has received much concern among its various toxic effects when given during developing period of brain. However, little is known about the neurotoxic effects and potential mechanisms of PFOS in the mature brain. Our study demonstrated the neurotoxicity and the potential mechanisms of PFOS in the hippocampus of adult mice for the first time. The impairments of spatial learning and memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…Moreover, a very lofty dose of PFOS (250 mg/kg) did not modify the dopamine concentration in the cerebellum or in the whole brain in male rats (Sato et al, 2009) but a later study showed a decrease of dopamine and DOPAC content in the caudate and putamen in mice treated with 10.75 mg of PFOS/kg/day for three months (Long et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, a very lofty dose of PFOS (250 mg/kg) did not modify the dopamine concentration in the cerebellum or in the whole brain in male rats (Sato et al, 2009) but a later study showed a decrease of dopamine and DOPAC content in the caudate and putamen in mice treated with 10.75 mg of PFOS/kg/day for three months (Long et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…It is known that the exposure to this perfluorinated compound induces several neuroendocrine alterations on the reproductive system (Joensen et al, 2013;L opezDoval et al, 2014L opezDoval et al, , 2015Zhao et al, 2014;van den Dungen et al, 2015;Zhang et al, 2015) and on the hypothalamic-pituitaryadrenal axis (Knox et al, 2011;Pereiro et al, 2014) as well as in the thyroid gland (Berg et al, 2015;Yu et al, 2015). Moreover, PFOS can cross the bloodebrain barrier (Austin et al, 2003) and be accumulated in the hypothalamus, (Austin et al, 2003) presenting neurotoxicity (Long et al, 2013;Pereiro et al, 2014;Dong et al, 2015). This chemical even seems to induce some alterations in neurochemical signaling (Eggers Pedersen et al, 2015) and could have behavioral effects, which were observed in East Greenland polar bears and in rats, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report showing the effects of oral exposure to PFOS on serotonin concentration and metabolism in several brain regions involved in the regulation of gonadotropin hormones: the anterior and mediobasal hypothalamus, and the median eminence. Although there are different studies showing PFOS effects on other biogenic amines such as dopamine and norepinephrine (Long et al, 2013;López-Doval et al, 2014), only Sato et al (2009) have studied the neurotoxicity of PFOS on serotonin concentration. These authors did neither find any change in the content of this indolamine in different brain areas nor in the whole brain, after a single oral PFOS exposure in rats and mice (Sato et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence that PFOA and PFOS can cause endocrine disruption and developmental toxicity has been reported (Steenland et al, 2010). It is a neurotoxic agent (Long et al, 2013), that can disrupt the neuroendocrine system activity, fact evidenced in mammals (Zhao et al, 2011a;Pereiro et al, 2014). It is also an animal carcinogen , besides, carcinogenicity to human is also suggested by epidemiological studies for workers employed in PFCs manufacturer (Alexander et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Effects observed included altered levels of excitatory amino acids in the brain of rats (Yang et al, 2009), and changes in neurotransmitter levels and increases in miniature post-synaptic currents (mPSC) along with inward calcium currents shown in cultured Sprague-Dawley rat hippocampal neurons (Liao et al, 2009). One study by using the Morris water maze found effects on learning and memory in mice at approximately 2 mg/kg/day (Long et al, 2013). Developmental neurotoxicity studies in rats found increased motor activity and decreased habituation and increased escape latency in the water maze test following in utero and lactational exposure to PFOS (Butenhoff et al, 2009).…”
Section: Animal Studiesmentioning
confidence: 99%